Connecting structure, dynamics and viscosity in sheared soft colloidal liquids: a medley of anisotropic fluctuations. Issue 1 (9th October 2015) - Westermeier, Fabian; Pennicard, David; Hirsemann, Helmut; Wagner, Ulrich H.; Rau, Christoph; Graafsma, Heinz; Schall, Peter; Paul Lettinga, M.; Struth, Bernd
Abstract : Simultaneous coherent X-ray and rheology experiments provide access to the transient structure, dynamics and viscoelastic behavior in repulsive colloidal suspensions. Abstract : Structural distortion and relaxation are central to any liquid flow. Their full understanding requires simultaneous probing of the mechanical as well as structural and dynamical response. We provide the first full dynamical measurement of the transient structure using combined coherent X-ray scattering and rheology on electrostatically interacting colloidal fluids. We find a stress overshoot during the start-up of shear which is due to the strong anisotropic overstretching and compression of nearest-neighbor distances. The rheological response is reflected in uncorrelated entropy-driven intensity fluctuations. While the structural distortion under steady shear is well described by Smoluchowski theory, we find an increase of the particle dynamics beyond the trivial contribution of flow. After the cessation of shear, the full fluid microstructure and dynamics are restored, both on the structural relaxation timescale. We thus find unique structure-dynamics relations in liquid flow, responsible for the macroscopic rheological behavior of the system.